(untitled) (Research, Society and Development, 2020)
This article aims to discuss the implementation process of the supervised curricular internship in clinical psychology, from the period of regulation of the profession, to the formalization of the National Curricular Guidelines for undergraduate courses in Psychology, based on the scientific literature. The stimulus for the preparation of this study is based on the recognition of the relevance of the improvement of student interns for the professional training of the Brazilian psychologist. An integrative literature review was used as a methodology, based on the search for scientific publications indexed in the databases: SciELO, PePSIC and ERIC. The following descriptors were used: clinical psychology, education, clinical internship, student and universities. At the end of the searches, 25 studies were selected that covered the Brazilian reality, between the years 1989 to 2020, which met the eligibility criteria to compose the article. It seeks to understand, throughout the article, the needs, the teaching and learning methods during the supervised internship, which must be aligned with the theory learned during the course with the practical actions of the Psychologist’s doing, so that it allows a clinical reasoning and an ethical stance. It is concluded that the study also proposes that it is essential that higher education institutions evaluate and renew the Clinic-school, so that students are trained and committed to providing support to society, since these institutions are responsible for providing training of highly qualified Psychologists and, in this conception, citizens should be able to act in the face of the typical demands of the 21st century.